Les premières sauvegardes de mosaïques antiques en France - Capucine Lemaître (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The restoration of mosaics begins in France with the notion of patrimony and the feeling of a common heritage to all citizens after the Revolution. But it also springs up in the fancy for italian archeological discoveries. The spreading of knowledge and techniques is carried out through oral exchanges and publications between antique dealers and erudition circles who are going to begin to be interested in vestiges on the french territory and try to ensure their safeguard. The study of two scholars'works, Pierre Schneyder who was the first manager of the Vienne museum in Isere and François Artaud who got together the first french collection of antique mosaics in the Palais des Arts in Lyon allows us to put forward the part of local elites who had to face numerous technical, economical and institutional restraints but who were, despite everything, the initiators of the first thoughts about the restoration of this archeological patrimony.